Sensori-Motor Learning with Movement Sonification: Perspectives from Recent Interdisciplinary Studies - Bevilacqua, Frédéric; Boyer, Eric O.; Françoise, Jules; Houix, Olivier; Susini, Patrick; Roby-Brami, Agnès; Hanneton, Sylvain (Frontiers in Neuroscience, 2016)
This article reports on an interdisciplinary research project on movement sonification for sensori-motor learning. First, we describe different research fields which have contributed to movement sonification, from music technology including gesture-controlled sound synthesis, sonic interaction design, to research on sensori-motor learning with auditory-feedback. In particular, we propose to distinguish between sound-oriented tasks and movement-oriented tasks in experiment involving interactive sound feedback. We describe several research questions and recently published results on movement control, learning and perception. In particular, we studied the effect of the auditory feedback on movements considering several cases: from experiments on pointing and visuo-motor tracking to more complex tasks where interactive sound feedback can guide movements, or cases of sensory substitution where the auditory feedback can inform on object shapes. We also developed specific methodologies and technologies for designing the sonic feedback and movement sonification. We conclude with a discussion on key future research challenges in sensori-motor learning with movement sonification. We also point out towards promising applications such as rehabilitation, sport training or product design.